Unbundling and higher education curriculum: a Cultural-Historical Activity Theory view of process. Issue 2 (17th February 2022) - Cliff, Alan; Walji, Sukaina; Jancic Mogliacci, Rada; Morris, Neil; Ivancheva, Mariya
ABSTRACT: The focus of this paper is on the contestations and dilemmas emergent in the higher education curriculum in a context of increasing processes of unbundling, digitisation and marketisation. The paper explores the notion of contestation through the theoretical lens of Cultural-Historical Activity Theory. It points to illustrative examples of this contestation from empirical data drawn from stakeholder research in South African higher education. The paper grapples with understandings of the concept of curriculum and argues how these have been shaped by – and are shaping – emergent meanings of the curriculum in an unbundling context. The argument is that these emergent meanings are a function of different explicit and tacit understandings of curriculum and what higher education offers to students. These understandings are deepened or modified by processes of unbundling. Empirical data from the research study show these understandings to be forming against the backdrop of powerful cultural and agentic forces and players.